2019
DOI: 10.1186/s12913-019-4468-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the costs and effectiveness of interventions to increase infant vaccination coverage in low- and middle-income countries

Abstract: BackgroundIn recent years, several large studies have assessed the costs of national infant immunization programs, and the results of these studies are used to support planning and budgeting in low- and middle-income countries. However, few studies have addressed the costs and cost-effectiveness of interventions to improve immunization coverage, despite this being a major focus of policy attention. Without this information, countries and international stakeholders have little objective evidence on the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 44 publications
0
47
0
Order By: Relevance
“…First, the studies we included in the analysis were heterogeneous in terms of the scope of costing, site selection, data collection methods, and the level of detail with which results were reported. This heterogeneity in costing study methods and reporting has been observed by prior reviews [51][52][53][54][55]. We attempted to deal with this by adopting an analytic strategy that allowed for differences in the cost categories and types of costs (i.e., financial vs. economic) reported.…”
Section: Discussionmentioning
confidence: 99%
“…First, the studies we included in the analysis were heterogeneous in terms of the scope of costing, site selection, data collection methods, and the level of detail with which results were reported. This heterogeneity in costing study methods and reporting has been observed by prior reviews [51][52][53][54][55]. We attempted to deal with this by adopting an analytic strategy that allowed for differences in the cost categories and types of costs (i.e., financial vs. economic) reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many other logistic deficiencies were reported including healthcare worker-related factors, the fragmentation of health information system, bad data management, and targets’ overreliance (Harrison et al 2020 ). Akin to that are the problems in the costs and cost-effectiveness of the immunization coverage in low- and middle-income countries (Munk et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this result should not be interpreted causally. Given the design of our study, we cannot conclude whether increasing facility-level service delivery volume would lead to a decrease in costs; the cost of increasing coverage will depend on the intervention used to do so [43] .…”
Section: Discussionmentioning
confidence: 93%